Tetralogy of Fallot at tbe Department of Paediatrics, Medical Faculty, Hasanuddin University, Ujung Pandang - J. M. C. H. Pelupessy; Husein Albar (Indonesian Pediatric Society, 1988)
A retrospective study was carried out on children with tetralogy of Fallot at the Department of Paediatrics, Medical Faculty, Hasanuddin University/Ujung Pandang General Hospital from January 1, 1982 to December 31, 1985 inclusive. The diagnosis of tetralogy of Fallot was based on the history, clinical and laboratory findings, chest radiograms and electrocardiograms. There were 10 children included consisting of 7 in- and 3 out- patients, ranging in age from 17 days to 10 years. All in-patients had protein energy malnutrition and or respiratory tract infection. Boy to girl ratio was 1 : 1,5. Cyanosis developed before the age of six months, clubbing of the fingers and toes manifested after one year of age while squatting became obvious after the age of two and a half years.